2019
DOI: 10.4028/www.scientific.net/nhc.27.31
|View full text |Cite
|
Sign up to set email alerts
|

Chrom<i>/</i>Nanocomposite ZrO<sub>2</sub>- Pillared Bentonite Catalyst for Castor Oil <i>(Ricinus communis) </i>Hydrocracking

Abstract: It has been carried out preparation of Chrom/Nanocomposite ZrO2-Pillared Bentonite catalyst with varying the amount of impregnating precursor at 0 to 3% (w/w). Material characterization of catalyst was carried out using X-ray Diffraction (XRD), X-ray Fluorescence (XRF), Infrared Spectroscopy (IR), Transmission Electron Microscope (TEM), Brunauer, Emmett, Teller (BET) and acidity measurement of ammonia-adsorption method. The results of research showed that pillarization was able to increase the basal spacing, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, non-edible vegetable oil such as Castor oil (Ricinus communis L.) could be used as alternate source, as this oil is not suitable for consumption because it contains ricin and ricinin (two highly toxic proteins). [5][6][7][8][9][10]. Castor oil also contains 80-90% ricinoleic acid that can be converted into hydrocarbon [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, non-edible vegetable oil such as Castor oil (Ricinus communis L.) could be used as alternate source, as this oil is not suitable for consumption because it contains ricin and ricinin (two highly toxic proteins). [5][6][7][8][9][10]. Castor oil also contains 80-90% ricinoleic acid that can be converted into hydrocarbon [9].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10]. Castor oil also contains 80-90% ricinoleic acid that can be converted into hydrocarbon [9].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the addition of pillaring agent Keggin ion [Al13O4(OH)24(H2O)12] 7+ reduces the diameter pore of bentonite due to the presence of micropores as a significant pore size after the intercalation process. In addition, this process also expands the basal spacing of bentonite [19,20,21]. The use of OH/Al ratios ranging from 1 to 10 mmol/g reduces bentonite pore diameter of from 6.8 to 3.38 nm.…”
Section: Figure 4 Xrd Pattern Of Natural Bentonite (A) Activated Bent...mentioning
confidence: 99%
“…29,30 Several new kinds of modied bentonite structures have been developed and demonstrated their potential in various catalytic processes. [31][32][33] Suseno 34 used Ni-Cu/ZrO 2 pillared bentonite in hydrocracking of palm oil to gasoline and revealed that the selectivity of gasoline fraction was inversely proportional to the Cu content of the catalyst. Wijaya et al 35 utilized Ni catalyst supported on sulfated ZrO 2 pillared bentonite and showed high activity and selectivity towards bio-gasoline from coconut oil conversion.…”
Section: Introductionmentioning
confidence: 99%